Audio steganography with enhanced LSB method for securing encrypted text with bit cycling - Enas Wahab Abood; Abdulhssein M. Abdullah; Mustafa A. Al Sibahe; Zaid Ameen Abduljabbar; Vincent Omollo Nyangaresi; Saad Ahmad Ali Kalafy; Mudhafar Jalil Jassim Ghrabta (Bulletin of Electrical Engineering and Informatics, 2022)
Data security pressing issue, particularly in terms of ensuring secure and reliable data transfer over a network. Encryption and seganography play a fundamental role in the task of securing data exchanging. In this article, both steganography and cryptography were combined to produce a powerful hybrid securing stego-system. Firstly, a text message is encrypted with a new method using a bits cycling operation to give a cipher text. In the second stage, an enhanced LSB method is used to hide the text bits randomly in an audio file of a wav format. This hybrid method can provide effectually secure data. Peak signal-to-noise ratio (PSNR), mean squared error (MSE) and structural similarity (SSIM) were employed to evaluate the performance of the proposed system. A PSNR was in range (60-65) dB with the enhanced least significant bit (LSB) and the SSIM had been invested to calculate the signal quality, which scored 0.999. The experimental results demonstrated that our algorithm is highly effective in securing data and the capacity size of the secured text. Furthermore, the time consumption was considerably low, at less than 0.3 seconds.